2017
DOI: 10.21037/mhealth.2017.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Applying a mobile survey tool for assessing lymphatic filariasis morbidity in Mtwara Municipal Council of Tanzania

Abstract: Background: A number of methods have been used to estimate lymphatic filariasis (LF) morbidity, including: routine programmatic data, cluster random surveys and the "town crier" method. Currently, few accurate data exist on the global LF morbidity burden in Tanzania. We aimed to estimate prevalence of lymphedema and hydrocele in Mtwara Municipal Council using mobile phone based survey. Methods:A cross-sectional survey was conducted among adults of Mtwara Municipal council with access to mobile phones. A sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…24 Estimates of the frequencies of the common presentations of these diseases and Buruli ulcer were obtained from literature review and expert opinion (Saunderson P, unpublished). 23,2527 For each confounding disease, the frequency of each presentation shared with Buruli ulcer was multiplied by the frequency of the presentation among Buruli ulcer cases, and the products were summed to generate a symptom overlap score (appendix). For each country, the symptom overlap scores for its endemic confounding diseases were summed, then downweighted if health expenditure was high or medium.…”
Section: Methodsmentioning
confidence: 99%
“…24 Estimates of the frequencies of the common presentations of these diseases and Buruli ulcer were obtained from literature review and expert opinion (Saunderson P, unpublished). 23,2527 For each confounding disease, the frequency of each presentation shared with Buruli ulcer was multiplied by the frequency of the presentation among Buruli ulcer cases, and the products were summed to generate a symptom overlap score (appendix). For each country, the symptom overlap scores for its endemic confounding diseases were summed, then downweighted if health expenditure was high or medium.…”
Section: Methodsmentioning
confidence: 99%
“…The studies were highly heterogeneous in their design, resulting from their heterogeneous objectives. Six (46%) studies [32][33][34][35][36][37] were reported to be community-based cross-sectional studies with the main objective of epidemiologically mapping a specific disease based on its clinical symptoms. Four out of 13 (31%) studies had different designs as follows: a mixed-methods approach to define challenges to be considered [38]; different implementation scenarios for a specific mHealth intervention [39]; the sustainability of an intervention [40]; and the process of developing a specific mHealth tool or assessing its usability [10,38].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Only eight different mHealth interventions were identified (Table 2). Three were based on sending SMS text messages between health workers and a central web system [33][34][35]37,39,41,43]. Text messaging is an easy technology to use and, as these studies show, is useful for motivating patients to complete treatments.…”
Section: Elements Included In the Mhealth Interventionsmentioning
confidence: 99%
“…Estimates of the frequencies of the common presentations of these diseases and BU were obtained from literature review and expert opinion. 24,[26][27][28][29] For each confounding disease, the frequency of each presentation shared with BU was multiplied by the frequency of the presentation among BU cases, and the products summed to generate a symptom overlap score (Table S1, Supplementary File).…”
Section: National Levelmentioning
confidence: 99%